Normative Databases for Imaging Instrumentation. Issue 6 (August 2015) - Realini, Tony; Zangwill, Linda M.; Flanagan, John G.; Garway-Heath, David; Patella, Vincent M.; Johnson, Chris A.; Artes, Paul H.; Gaddie, Ian B.; Fingeret, Murray
Abstract : Purpose: To describe the process by which imaging devices undergo reference database development and regulatory clearance. The limitations and potential improvements of reference (normative) data sets for ophthalmic imaging devices will be discussed. Method: A symposium was held in July 2013 in which a series of speakers discussed issues related to the development of reference databases for imaging devices. Results: Automated imaging has become widely accepted and used in glaucoma management. The ability of such instruments to discriminate healthy from glaucomatous optic nerves, and to detect glaucomatous progression over time is limited by the quality of reference databases associated with the available commercial devices. In the absence of standardized rules governing the development of reference databases, each manufacturer's database differs in size, eligibility criteria, and ethnic make-up, among other key features. Conclusions: The process for development of imaging reference databases may be improved by standardizing eligibility requirements and data collection protocols. Such standardization may also improve the degree to which results may be compared between commercial instruments.